2017
DOI: 10.1111/ssm.12202
|View full text |Cite
|
Sign up to set email alerts
|

Geometry‐Related Children's Literature Improves the Geometry Achievement and Attitudes of Second‐Grade Students

Abstract: Use of mathematics-related literature can engage students' interest and increase their understanding of mathematical concepts. A quasi-experimental study of two second-grade classrooms assessed whether daily inclusion of geometryrelated literature in the classroom improved attitudes toward geometry and achievement in geometry. Consistent with the hypothesis, only the students in the classroom with a strong emphasis on geometry-related children's literature showed a significant improvement in their attitudes ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…Abstract mathematical concepts are embedded in informal meaningful real-world contexts that children can relate to and better comprehend. This view is supported by a range of empirical studies, for example, those conducted by McAndrew, Morris, and Fennell (2017), Jennings et al (1992) and Van den Heuvel-Panhuizen and Elia (2011), all of which have found that children's mathematical ability increased when mathematics was taught together with literature.…”
Section: Children's Literature and Mathematicsmentioning
confidence: 90%
“…Abstract mathematical concepts are embedded in informal meaningful real-world contexts that children can relate to and better comprehend. This view is supported by a range of empirical studies, for example, those conducted by McAndrew, Morris, and Fennell (2017), Jennings et al (1992) and Van den Heuvel-Panhuizen and Elia (2011), all of which have found that children's mathematical ability increased when mathematics was taught together with literature.…”
Section: Children's Literature and Mathematicsmentioning
confidence: 90%
“…This is crucial particularly when, Trakulphadetkrai et al (2020) have found connections between pupils' mathematical and language abilities. Research over the past decades have consistently shown that language and literacy, particularly in the form of children's literature, can be used to foster pupils' mathematical thinking (Van den Heuvelpanhuizen et al, 2016) and also positive attitudes towards the subject (McAndrew et al, 2017). Ewing Monroe et al (2018) carried out a systematic analysis of research that reported on the effects of using children's literature in teaching mathematics at elementary level.…”
Section: Integrating Children's Literature With Mathematicsmentioning
confidence: 99%
“…Muir et al (2017) describe the groundwork for using math literature during math instructions and offers math activities and children's books in their book to use for teaching many elementary math concepts using picture books in today's classrooms. McAndrew et al (2017) found in their quasi-experimental study that by using children's literature, specifically, Geometry-related children's literature improves the geometry success and attitudes of 2 nd -Grade students. Weinstein (2017) did an all-encompassing literature review on how using children's literature is effective in covering the new Common Core State Math Standards and gives an all-inclusive list of children's literature to use to model and teach many math concepts covered today in elementary school.…”
Section: Using Children's Literature To Teach Mathematicsmentioning
confidence: 99%